Animal abuse, biotechnology and species justice - Rodríguez Goyes, David (Theoretical criminology, 2018)
Generally, in the modern, western world, conceptualizations of the natural environment are associated with what nature can offer us—an anthropocentric perspective whereby humans treat nature and all its biotic components as ‘natural resources'. When nature and the beings within it are regarded purely in utilitarian terms, humans lose sight of the fact that ecosystems and nonhuman animals have intrinsic value. Most biotechnological use of nonhuman animals is informed by an instrumental view of nature. In this article, we endeavour to broaden the field of animal abuse studies by including in it the exploration of biotechnological abuse of animals. We analyse the issue by discussing it in relation to differing philosophical starting points and, in particular, the rights and justice theory developed within green criminology.